Nonlinear optical properties of a one-dimensional coordination polymer. Issue 11 (6th March 2017) - Liu, Min; Quah, Hong Sheng; Wen, Shuangchun; Wang, Junyong; Kumar, P. Sanjay; Eda, Goki; Vittal, Jagadese J.; Ji, Wei
Abstract : A one-dimensional coordination polymer shows nonlinear properties of PL, SHG and THG. Abstract : Nonlinear optical materials with functions of generating second harmonic generation (SHG) or/and third harmonic generation (THG) have attracted great interest because of their applications in extending coherent light frequencies from the given lasers. Here we report on a one-dimensional coordination polymer, which is capable of generating SHG, THG, and multi-photon-excited photoluminescence (PL) depending on an excitation wavelength in the range from 800 nm to 1500 nm. The coordination polymer consists of two ligands, namely (1) benzoate and (2) trans, trans -9, 10-bis(4-pyridylethenyl)anthracene (An2Py). The second order optical nonlinearity, d eff, of the single crystal has been determined to be 6.4 pm V −1, at 1200 nm, while the third nonlinear optical susceptibility, χ (3), is measured to be ∼8 × 10 −11 esu at 1500 nm.